Executive function abilities in cognitively healthy young and older adults—A cross-sectional study - Idowu, Mojitola I.; Szameitat, Andre J. (Frontiers in Aging Neuroscience, 2023)
A prominent feature of cognitive aging is the decline of executive function (EF) abilities. Numerous studies have reported that older adults perform poorer than younger adults in such tasks. In this cross-sectional study, the effect of age on four EFs, inhibition, shifting, updating, and dual-tasking, was examined in 26 young adults (mean 21.18 years) and 25 older adults (mean 71.56 years) with the utilization of a pair of tasks for each EF. The tasks employed for DT were the Psychological Refractory Period paradigm (PRP) and a modified Test for Everyday Attention (TEA), for inhibition the Stroop and Hayling sentence completion test (HSCT), for shifting a task switching paradigm and the trail making test (TMT), and for updating the backward digit span (BDS) task and a n-back paradigm. As all participants performed all tasks, a further aim was to compare the size of the age-related cognitive decline among the four EFs. Age-related decline was observed in all four EFs in one or both of the tasks employed. The results revealed significantly poorer performance in the older adults in the response times (RTs) of the PRP effect, interference score of the Stroop, RT inhibition costs of the HSCT, RT and error-rate shifting costs of the task switching paradigm, and the error-rate updating costs of the n-back paradigm. A comparison between the rates of decline revealed numerical and statistically significant differences between the four EFs, with inhibition showing the greatest decline, followed by shifting, updating, and dual-tasking. Thus, we conclude that with age, these four EFs decline at different rates.